Pengaruh Capital Structure terhadap Profitabilitas dengan Tax Planning sebagai Variabel Intervening - Puspita, Diana; Hendri, Nedi; Retnaning Rahayu, Sri (Expensive: Jurnal Akuntansi dan Keuangan, 2025)
It was quantitative research with quantitative descriptive methods. This research was aimed at providing empirical evidence about the influence of Capital structure on profitability with tax planning as an intervening variable. The determination of samples used through purposive sampling, so that 25 companies were obtained, with a total of 75 observations. The testing method in this research used path analysis (path analysis) with eviews application 12. The results of this study show that Debt to Asset Ratio (DAR) has a direct effect on tax planning. Long-term Debt to Equity Ratio (LDER) has no direct effect on tax planning. Debt to Asset Ratio (DAR) had no direct effect on profitability. Long-term Debt to Equity Ratio (LDER) had no direct effect on profitability. Tax planning did not have a direct effect on profitability. Debt to Asset Ratio (DAR) and Long-term Debt to Equity Ratio (LDER) had no a simultaneous effect on tax planning. Debt to Asset Ratio (DAR), Long-term Debt to Equity Ratio (LDER) and tax planning had no simultaneous effected on profitability